RESULTS OF PIKE PERCH SANDER LUCIOPERCA INTRODUCTION IN LAKE KHANKA - M. E. Shapovalov (Известия ТИНРО, 2018)
Pike perch was introduced into Lake Khanka in 1970–1978. The introduction was founded on concept of low commercial productivity of the lake prevailed in those times. For the past 50 years, the species acclimatized successfully in the lake. However, the process of its naturalization was not easy, with periodic disappearance from the catches succeeded by blooms. In recent years, the species became one of the most important objects of commercial fishery. Studies of its ecology show that Lake Khanka environments are rather good for pike perch breeding, in particular the food supply for all stages of its larvae and juveniles. As the result, pike perch in Lake Khanka is distinguished by earlier puberty in comparison with the same species in the Amur River and the Curonian Lagoon. Its adults consume low-valued fish and shrimps abundant in the lake. After successful acclimatization in Lake Khanka, pike perch penetrated through the Sungacha to the Ussuri River by 1985, and further to the Amur where in decade it extended upstream to the Bira tributary and downstream to Yelabuga village. Currently, pike perch is a common species in catches on the middle and low Amur from Blagoveshchensk to Mago, i.e. > 1 500 km from Lake Khanka.